The function of the National Debt Registerin counteracting payment gridlocks in Poland - Bekas-Nowak, Monika (Publishing House of the Wrocław University of Economics, 2009)
According to the author the National Debt Register undoubtedly plays a significant part in the process of economic information exchange. What is more, the operations of the Bureau are being approved of by the whole society. Conducted research and statistics prove that the National Debt Register has become a crucial element of the Polish economic life. Within European Union public information registers concerning financial standing of enterprises and consumers have existed for many years, and have constituted an important source of information about potential customers. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 49-56